Photovoice methodology to promote education for sustainable development - Muller, I. (South African Journal of Higher Education, 2023)
Education for Sustainable Development is best addressed in a spontaneous, place-based context where participants have the freedom of choice. Such an opportunity occurred with the Ripple Effect, a global initiative that allows participants to indicate the role of water in their living experience. Preservice teachers embraced the chance to display their interpretation of the role of water in their lives by participating in a Photovoice project. Photovoice is a chameleon in action research as it not only provides a research methodology but can serve as a reflection tool to enhance learning. The preservice teachers concluded, after reflecting on the role of water in their daily lives, that they are citizen scientists who can utilize place-based learning opportunities. The Photovoice project allowed for affective learning as well as an opportunity to face communal problematic scenarios regarding water.